EFFECT OF WORK DISCIPLINE AND PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT THE MANAGEMENT AGENCY OF WISMA GADING PERMAI APARTMENTS NORTH JAKARTA - Pratama, Angga (International Journal of Social and Management Studies, 2022)
The purpose of this study was to determine the effect of work discipline and physical work environment on employee performance at the Wisma Gading Permai Apartement Management Agency in North Jakarta, either partially or simultaneously. The method used is quantitative. The sampling technique used was saturated sampling and the sample in this study was 90 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The result of this study is that work discipline has a significant negative effect on employee performance. Hypothesis test obtained tcount > ttable. Thus, H0 is rejected and H1 is accepted, meaning that there is a significant negative effect of work discipline on employee performance. The physical work environment has a significant effect on employee performance. Hypothesis test obtained tarithmetic > ttable. Thus, H0 is rejected and H2 is accepted, meaning that there is a significant effect of the physical work environment on employee performance. Work discipline and physical work environment simultaneously have a significant effect on employee performance with the regression equation Y = 24,897 + -0.138X1 + 0.495X2. The value of the coefficient of determination is 52.9% while the remaining 47.1% is influenced by other factors. Hypothesis test obtained value of farithmetic > ftable or (48,810 > 2,710). Thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant influence of work discipline and physical work environment on employee performance.